Global health governance performance during Covid-19, what needs to be changed? a delphi survey study - Wafa Abu El Kheir-Mataria; Hassan El-Fawal; Sungsoo Chun (BMC, 2023)
Abstract Background Covid-19 is not the first pandemic to challenge GHG. Preceding outbreaks and epidemics were sources of continuous debate on GHG leadership and structure resulting in its current structure. However, Covid-19 proved the presence of many deficits in the current GHG. The response to the Covid-19 pandemic is a cumulative result of all policies and actions of different governments and agencies active in global health. Assessing how Covid-19 is being handled globally provides lessons for ensuring better performance in facing upcoming outbreaks. This study has three main objectives: first, to evaluate the performance of GHG during Covid-19 in general and in relation to Covid-19 vaccine equity in particular. Second, to identify the reasons behind this performance; and third, to propose prospective changes in GHG for better performance. Methods A cross-sectional research design using the Delphi method was applied. A panel of experts participated in the three-round Delphi surveys. Their scores were used to perform consensus, performance and correlation analysis. Results GHG performance limited the achievement of Covid-19 vaccines' global equity. GHG performance is a product of the existing GHG system, its actors and legal framework. It is a collective result of individual GHG actors' performance. The most influential actors in decision-making regarding Covid-19 vaccine are the vaccine manufacturers and governments. While the most invoked power to influence decision are economic and political powers. Covid-19 decisions underlying value, although had human right to health at the base, overlooked the concept of health as a global public good and was skewed towards market-oriented values. GHG mal-performance along with its underlying factors calls for four main changes in GHG structure: assigning a clear steward for GHG, enhanced accountability, centralized authority, more equitable representation of actors, and better legal framework. Conclusion GHG structure, actors' representation, accountability system, and underlying priorities and value require future modification for GHG to achieve better future performance and higher health equity levels.